GEOGRAPHY OF CRIME AND ITS ESSENCE, MAIN DIRECTIONS (Scientific journal of the Fergana State University, 2023)
In this article, the geography of crime and its nature, main directions, territorial differences of crime and geographical factors affecting crime are considered, analyzed and conclusions are given.